Exploring the Spatial-Temporal Microbiota of Compound Stomachs in a Pre-weaned Goat Model - Lei, Yu; Zhang, Ke; Guo, Mengmeng; Li, Guanwei; Li, Chao; Li, Bibo; Yang, Yuxin; Chen, Yulin; Wang, Xiaolong (Frontiers in Microbiology, 2018)
Ruminant animals possess a characteristic four-compartment stomach (rumen, reticulum, omasum, and abomasum) that is specialized for pre-intestinal digestion of plant materials. Of these four compartments, the rumen is the largest. The rumen’s diverse microbial community has been well studied. However, the current understanding of microbial profiles in the reticulum, omasum and abomasum are lacking. In the present study, fluid samples from the reticulum, omasum, and abomasum of goats at 3, 7, 14, 21, 28, 42 and 56 days after birth, as well as the negative controls (NC) used for microbial DNA extraction, were subjected to 16S rRNA sequencing. By filtering OTUs in NC, distinct temporal distributions of microbes were observed in the different compartments, we showed that the OTUs in control samples had a large effect to the samples with low microbial density. In addition, Proteobacteria gradually decreased with age from days 3 to 56 in all 3 compartments, and the relative abundance of Bacteroidetes increased from 24.15% (Day 3) to 52.03% (Day 56) in abomasum. Network analysis revealed that Prevotellaceae_UGG-03 and Rikenellaceae_RC9 were positively correlated with Prevotella_1, lending support to the well understood fact that cellulose is well digested in compound stomachs prior to the rumen. Pathway analysis revealed that gene expression in abomasum at Day 3 were primarily related to Glycolysis/Gluconeogenesis and Pyruvate metabolism, suggesting that colostrum digestion is the dominant function of the abomasum at an early age. These findings combined with other recent rumen microbiota data show that the microbiome landscape represents three distinct stages in ruminant stomachs. The first stage is to gain access to external microorganisms at Day 0-14, the secondary stage is for microbial transition at Day 14 - 28, and the third stage is for exogenous and endogenous microbial colonization beyond Day 28 of age. Our results provide insight into microbiota dynamics in ruminant stomachs, and will facilitate efforts for the maintenance of gastrointestinal balance and intervention with starter diets in juvenile ruminants during early development.